Seasonal work : [large type] stories - Lippman, Laura, 1959- (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
"In a suspenseful collection of stories featuring fierce women--including one never-before-published novella--New York Times bestseller Laura Lippman showcases why she is one of today's top crime writers"--